Herpes zoster after left nephroureterectomy for renal carcinoma: a case report - Yuren Zhang; Jie Li; Qing Ni (BMC Infectious Diseases)
Abstract Background Diabetes and malignant tumors often lead to abnormal immune function, increasing susceptibility to herpes zoster and severe post-herpetic neuralgia. Renal insufficiency following renal cell carcinoma surgery can be compounded by treatment with nephrotoxic antiviral drugs. There have also been case reports of herpes zoster occurring at the surgical site. Case presentation A 68-year-old man developed herpes zoster at the surgical site and severe neuralgia following left nephroureterectomy for left kidney clear cell carcinoma accompanied by postoperative renal insufficiency. After treatment with brivudine, the herpes was controlled, and neuralgia began to subside by day 3, with crust formation occurring by day 9. Conclusions Postoperative nerve injury and regeneration may influence varicella-zoster virus latency. This case indicates that brivudine is an effective treatment for herpes zoster in patients with chronic renal insufficiency.